The role of vitamin D in slipped capital femoral epiphysis in children and adolescents: a retrospective case-control study - Ning, Peng; Lin, Shuting; Geng, Huiyu; Liu, Tianjing (Frontiers in Endocrinology, 2025)
ObjectiveTo explore the correlation between vitamin D levels, related endocrine/metabolic factors, and the risk of slipped capital femoral epiphysis (SCFE) in children and adolescents, and to assess whether vitamin D levels are associated with SCFE severity.MethodsA retrospective case-control study was conducted from March 2014 to October 2023 in Shengjing hospital. Patients diagnosed with SCFE were categorized as the SCFE group. The control group consisted of healthy children matched by gender, age, weight, height, body mass index (BMI), and date of blood tests at a 1:2 ratio from the pediatric developmental clinic. The analysis included relevant laboratory tests such as 25-hydroxyvitamin D (25(OH)D), hemoglobin (Hb), serum alkaline phosphatase (ALP), calcium (Ca), phosphorus (P), and magnesium (Mg), etc. Univariate and multivariate conditional logistic regression analyses were conducted to identify factors associated with SCFE, with a particular focus on the correlation between 25(OH)D levels and the risk of SCFE. The study also explored whether these factors were correlated with SCFE severity, determined by measuring the slip angle and displacement on the anteroposterior pelvic or frog-leg lateral views.ResultsOne hundred and twenty subjects were finally included, with 40 SCFE patients (36 males, 4 females) and 80 controls (72 males, 8 females). There were no significant differences in gender, age, weight, height, BMI, Hb, albumin (ALB), creatinine (Cr), free triiodothyronine (FT3), thyroid stimulating hormone (TSH), Ca, and P (P>0.05). Significant differences were found in 25(OH)D, ALP, free thyroxine (FT4), and Mg (P<0.05). The SCFE group had lower 25(OH)D and ALP levels but higher FT4 and Mg. Univariate analysis showed that 25(OH)D, FT4, and ALP were associated with SCFE, but multivariate analysis indicated only 25(OH)D had a significant correlation (P<0.05). 25(OH)D levels were not linked to SCFE severity (P>0.05).ConclusionsThe results of this study indicate that a higher level of vitamin D is associated with a decreased risk of SCFE, suggesting potential benefits of vitamin D sufficiency. However, no correlation was observed between 25(OH)D levels and the severity of SCFE. Serum FT4 and ALP also seem to have some association with SCFE, but the clinical significance is unproven. Future multi-center studies in various regions are necessary to further validate the protective role of vitamin D against SCFE.